Introdução do conceito de função a partir do contexto da produção do fumo com vistas à aprendizagem significativa crítica - Dias, Clara Celina Ferreira (2019)
This work is result of a master research that had as main objective to investigate the process of teaching and learning of the mathematical concept linear function, in the context of tobacco production, in a class of 1st year of high school. The research was developed with a group of thirty-two students, children of farmers, most of them tobacco growers in the E. E. E. Presidente Afonso Pena, in Paraíso do Sul / RS. It is a qualitative research that presents as a methodology the use of pedagogical interventions, whose instruments of data collection were questionnaires, the researcher's logbook, class diary, class notebooks of students, conceptual maps, textbooks and pedagogical interventions. As a theoretical reference, it was sought support in authors that deal with Mathematical Education focusing on Ausubel's Significant Learning theory (2003) and Moreira's Critical Significant Learning (2010). Seven pedagogical interventions were developed and developed from the context of the production of tobacco to learn the concept of linear function. From the analyzed data, significant learning indicators were observed attending to most of the principles that guide critical learning. However it is important to note that for the student to learn meaningfully, it is not enough to have a significant instructional material, it also implies that he wants to learn in a meaningful way. In pedagogical interventions, a viable and effective tool for articulating theory to practice, that is, through them, it is possible to evidence the applicability of everyday mathematical concepts and to favor dialogue between students and teachers in a critical and reflexive way. It is suggested to expand this study in other contexts conducted for interdisciplinary projects.